Bridge Builders to Health Equity: The High School Community Health Worker Training Program - Arletha Williams-Livingston; Christopher Ervin; Gail McCray (Journal of the Georgia Public Health Association, 2020)
BackgroundDuring the summers of 2016- 2019, Morehouse School of Medicine (MSM) with the support of community partners, developed, piloted and implemented an innovative Community Health Worker Training Program for High School students (HSCHW). Training high school community health workers can impact health and social disparities in underserved populations and demonstrates pipeline of future workers in community health and other health careers. The program has achieved promising outcomes, and access to the program model has been requested many universities and community-based organizations. MethodThe HSCHW training consists of summer classroom instruction, field instruction and monthly continuing education during the school year. The students are trained in CHW core competencies through a combination of online curriculum, interactive classroom experiences, and field activities provided by community partners, multidisciplinary MSM clinical instructors, and graduate student interns. Results 77 high school students from metropolitan Atlanta High Schools and rural Columbus, GA have been trained as CHWs in the HSCHW program. Students are ages 15-18 and are rising sophomores to recent high school graduates. All participants (100%) were from economically disadvantaged communities. Sixteen school-based and community-based health improvement projects have been developed and implemented by teams of trained HSCHWs. Additionally, over 300 individuals (family and community members) received monthly health monitoring by trained HSCHWs. ConclusionsOverall, the HSCHW program models the engagement of community partners in translational educational initatives to support community transformation. It can be a giant leap toward improved population health and achieving health equity in underserved communities. It has had a tremendous impact on the youth themselves, their families, and the communities in which they live. In communities with disparate prevalence of chronic disease and unhealthy behaviors, early exposure may mitigate exacerbation or early onset of disease among the participants and their families. High School Community Health Workers are bridges to health equity.